Hubungan Peran Keluarga terhadap Kejadian Stunting: Literature Review - Syofyanengsih Syofyanengsih; Nur Alam Fajar; Novrikasari Novrikasari (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Malnutrition is a problem experienced by every country in the world, including Indonesia. This study aims to analyze family factors related to stunting in Indonesia. Five databases (Scopus, Science Direct, EBSCO, ProQuest, and PubMed) were explored to find relevant articles published from 2015 to 2020. The Boolean search used “factor”, “dwarfing”, “parent” and “Indonesia” in the title, abstract, or keywords. The inclusion criteria were: original articles in English; sources from journals; research locations in the territory of Indonesia; families with children < 5 years; and available in full text. This systematic review used the PRISMA guidelines. The determinants were analyzed based on the WHO conceptual framework for stunting. We identified 120 articles, and 20 were deemed relevant for this systematic review. The main research design for these 20 journals is cross sectional. This review shows that stunting in Indonesia is still very high. Family factors related to stunting in Indonesia include low caregiver education, low household welfare, poor nutrition during pregnancy, poor sanitation and inadequate water supply, smoking father, young mother and poor parenting. The results of the study became the basis for developing family centered care for stunting.